مسائل إفرادية خلافية بين ابن هشام وابن مالك - جاهمي, آمنة (University of Eloued جامعة الوادي, 2024)
ولّد الصراع القائم بين المدارس النحوية، مسائل خلافية نحوية شكلت جوا مشحونا بين أعلامها، ما جعل كل فريق يسعى بكل ما أوتي من علم لتقديم الحجج والأدلة المثبتة لرأيه، لذا سنعالج في هذا المقال جملة من المسائل النحوية الخلافية بين ابن مالك في كتابه:" تسهيل الفوائد وتكميل المقاصد "،وابن هشام في كتابه: "مغني اللبيب عن كتب الأعاريب"، لأن كلا منهما يمثل مدرسة شبه مستقلة في الرؤية والمنهج. الكلمات المفتاحية: النحو العربي، المسائل النحوية الخلافية، ابن هشام، ابن مالك. Abstract: The conflict between the grammatical schools generated controversial grammatical issues that formed a charged atmosphere between their scholars, which made each team strive with all its knowledge to provide arguments and evidence proving its opinion, so we will address in this article a number of controversial grammatical issues between Ibn Malik in his book: “Facilitation Benefits and Takmel al-Maqasid” and Ibn Hisham in his book: “Mughni al-Labib on the books of the Arabs,” because each of them represents a semi-independent school in vision and method. Keywords: Arabic grammar, grammatical issues, Ibn Hisham, Ibn Malik.
مقال. مجلة علوم اللغة العربية وآدابها. مج16 . ع.01. جامعة الوادي
Keywords: النح; العربي